Pengaruh Penempatan Kerja Dan Kompensasi Terhadap Kepuasan Kerja Karyawan Kontrak Pada Pt. Aluprima Pacific Industries Kab. Serang - Isabela, Metha; Lesmana, Ihwan Satria; Romli, Ombi (CV. Kalimasada Group, 2024)
Human Resources (HR) is the most important factor in an organization or company and is one of the factors that can be a source of advantage to achieve efficiency and effectiveness in running its business. This study aims to determine whether the influence of job placement and compensation simultaneously affects employee job satisfaction at PT. Aluprima Pacific Industries. This research uses a quantitative method, which can be interpreted as a research method based on the philosophy of positivism, used to study specific populations and samples. The results of this study indicate that job placement and compensation simultaneously affect job satisfaction. This is known from the results of determining the F-table value, as the limit of the acceptance or rejection area of the hypothesis, which can be done with the formula (df) = n-k where n = number of samples, while k = number of independent variables with a significant level of α = (0.05), resulting in an F-table value of 3.18. Because the calculated F-value > F-table (18.232 > 3.18) and the significance value is below 0.05 with a significance level of 0.000 < 0.05. Overall, proper job placement and adequate compensation are key factors that contribute to employee job satisfaction at PT. Aluprima Pacific Industries. Therefore, the company is advised to continue paying attention to and improving these two aspects to create a better and more productive work environment